Motivation for luxury consumption in the fragrance industry: a study on Romanian and Bulgarian Millennials - Yaneva, Mihaela (2015)
The purpose of this report is to generate valuable consumer insight about purchases in the luxury fragrance industry by Bulgarian and Romanian Millennials. The study also focuses on the concepts of acculturation and ethnic identification and their mediating effect on the purchase of luxury perfumes. The literature review examines the topic based on previous work in the fields of psychology, marketing, consumer behavior and economics and presents three conceptual frameworks for creating value for luxury goods. Primary data was collected from 99 participants via self-completion surveys. The results revealed a strong effect of craftsmanship and outer-directed symbolism on the intention to buy a designer fragrance. A second small-scale study was executed in order to test the behavioral difference between immigrants and non-immigrants in terms of motivation for perfume purchase. Acculturation and ethnic identity proved to be significant mediators in the consumption process as they impact materialistic values. The project concludes with discussion of the implications for marketers and directions for further research.